31‐1: Distinguished Paper: Measurement and Categorization of Alternate Subpixel Layout Near‐Eye Display Systems. Issue 1 (29th May 2019) - Hoffman, David M.; McKenzie, Chris; Koprowski, Brion; Iqbal, Asif; Balram, Nikhil
Abstract : We analyzed displays with alternate subpixel layouts to assess the effective detail size that they can reproduce. The measurements can then be used to classify the display to an appropriate XR system tier. Responsive application design can then tailor content for the best possible experience on each system tier.